(a) A, B, C

(b) B, C, A

(c) C, B, A

(d) C, A, B

Want to ask us a question? Click here

Browse Questions

Ad |

0 votes

0 votes

Answer: B, C, A

Let $\Delta H_f (A) = x$ kJ/mol

$A\longrightarrow B$ ; $\Delta H$ = + 24 kJ/mol

$\Delta H = \Delta _f H(B) - \Delta_fH(A)$

$\Rightarrow \Delta _f H(B) =\Delta H + \Delta_fH(A)$

$\Rightarrow \Delta_f H(B) = (x+24) $ kJ/mol

$B\longrightarrow C$ ; $\Delta H$ = - 18 kJ/mol

$\Delta H = \Delta _f H(C) - \Delta_fH(B)$

$\Rightarrow \Delta _f H(C) =\Delta H + \Delta_fH(B)$

$\Rightarrow \Delta_f H(B) = [-18+(x+24)] $ kJ/mol = $(x+6)$ kJ/mol

$\therefore$ In decreasing order $B>C>A$

Ask Question

Take Test

x

JEE MAIN, CBSE, NEET Mobile and Tablet App

The ultimate mobile app to help you crack your examinations

...